1988
DOI: 10.1111/j.1442-9993.1988.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of termite communities in the Australian tropics

Abstract: The distributions of 50 species of termites across five habitat types in Kakadu National Park are described. Open forests are riehest in speeies and monsoon forests are species-poor. The greatest diversity of termites is associated with infertile soils and is probably related to the enhanced role of termites in these nutrientimpoverished sites. Only the riehness of livewood feeders is associated with disturbance in the form of water buffalo impaet. Pew relationships with physical characteristics of the soil we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 20 publications
3
75
3
Order By: Relevance
“…This contrasts with the findings of Braithwaite et al (1988) who found a significant negative correlation between termite species richness (as richness of dead wood, decayed wood and litter-feeding species) and projected foliage cover. These authors also found significant negative correlations between the species richness of decayed wood and litter feeders and harvesters with the depth of the litter layers.…”
Section: Species Richnesscontrasting
confidence: 83%
See 1 more Smart Citation
“…This contrasts with the findings of Braithwaite et al (1988) who found a significant negative correlation between termite species richness (as richness of dead wood, decayed wood and litter-feeding species) and projected foliage cover. These authors also found significant negative correlations between the species richness of decayed wood and litter feeders and harvesters with the depth of the litter layers.…”
Section: Species Richnesscontrasting
confidence: 83%
“…This species feeds on living, dead and partly decayed wood and woody litter (Braithwaite et al 1988). …”
Section: Assemblage Structure and Ecological Strategiesmentioning
confidence: 99%
“…These termites attack live trees usually from underground or occasionally through broken stems. It extends galleries through the heartwood, often eating into sapwood as well, producing a hollow pipe the entire length of the bole (Braithwaite et al, 1988;Andersen et al, 2005) and even into smaller branches and throughout the larger root system (Werner and Murphy, 2001 and unpublished data).…”
Section: Termitesmentioning
confidence: 94%
“…The most common tree-piping termite species in undisturbed savanna woodlands of the region is Coptotermes acinaciformis (Froggatt), accounting for more than 90% of the pipes in trees growing in natural areas (Fox and Clark, 1972;Braithwaite et al, 1988;Hodda, 1992;Andersen et al, 2005). These termites attack live trees usually from underground or occasionally through broken stems.…”
Section: Termitesmentioning
confidence: 98%
“…Further, Hodda (1992), in a survey of termites in Kapalga, found that the decrease in total herbaceous vegetation and the relative shift to annual grasses negatively affected ''harvester'' termites which preferentially feed on perennial grasses. Conversely, the species richness and abundance of termites that feed on the wood of live trees or forage in wood litter (and on buffalo dung) were positively correlated with buffalo presence (Braithwaite et al 1988, Hodda 1992.…”
Section: Savanna Woodlands and Open Forestmentioning
confidence: 98%